Development of Doratoon-Based Video Animations Material of Algebra - Khofifatul, Khusna; Ikashaum, Fertilia (JPMI (Jurnal Pendidikan Matematika Indonesia), 2024)
This research aims to produce Doratoon-based animated math learning videos that are deemed feasible and practical for algebra material. This study is classified as development research or qualitative descriptive analysis. The development research is designed using the Hannafin and Peck development model, which includes the stages of needs analysis, design analysis, development analysis, and implementation. The results of this research show that the media experts obtained an average percentage score of 82%, indicating "Good" quality, while the subject matter experts obtained an average percentage score of 87.5%, indicating "Very Good" quality. Furthermore, the students' response to the development of animated video learning media for matrix material during the product trial received a response of "interesting" with an average percentage score of 83%. Therefore, it can be concluded that the development of Doratoon-based animated video learning media for algebra material is considered suitable and engaging for use in school learning.